Peran Perserikatan Bangsa-Bangsa dalam Kaitannya dengan Penegakan Hukum Oleh Mahkamah Pidana Internasional (Prospek dan Tantangan) - Damayanti, Novy Septiana (Faculty of Law, Universitas Pattimura, 2020)
International law in its development moves dynamically according to international community interactions. In the development of international law has spawned an international organization, namely the United Nations (UN). International courts relating to the UN status. The UN has laid the framework of the kosnstitusionic on the underlying instrument of the Charter with the determination of all the members of the UN to avoid the recurrence of World War threats that have twice occurred and have caused A threat to all mankind. THE un-formed International Criminal Court is backed by many demands for justice for its extraordinary crimes (the most serious crime). The International Criminal Court aims to end impunity for perpetrators of gross human rights violations and to give a share of the prevention of the most serious crimes against human rights under international law, as well as Ensure international justice and support the achievement of objectivesof the United Nations Charter principles. Based on the description the problem that will be discussed in this article is the role and authority of THE International Organization (PBB) in maintaining international peace and security in resolving the problems that Conducted by the International Criminal Court (ICC).This Writing uses legal research methods is normative with the research of secondary data and described descriptively.